New species of the genus Lethrus Scopoli, 1777 (Coleoptera: Geotrupidae: Lethrinae) from Fergana Valley, Kyrgyzstan - Shapovalov, Andrey M. (Zootaxa, 2022)
Lethrus (Autolethrus) toropovi Shapovalov, new species is described from the north of the Fergana Valley (Kyrgyzstan, central part of the Chatkal Mountain Range). New species is characterized within the Lethrus sulcipennis-group by the characters of the mandibular processes.